Seasonal dynamics of the soil microbial community: assimilation of old and young carbon sources in a long‐term field experiment as revealed by natural 13C abundance. (23rd November 2015) - Börjesson, G.; Menichetti, L.; Thornton, B.; Campbell, C. D.; Kätterer, T.
Summary: Microbial biomass is a small part of the total soil organic carbon (SOC) pool, but plays a major role in its turnover. A field experiment in Sweden, amended with different mineral and organic materials since 1956, was changed from continuous C3 plants to C4 vegetation (silage maize) in 2000. In 2012, soil samples from three fertilizer treatments (calcium nitrate, calcium nitrate plus straw and sewage sludge) and two controls (bare fallow and cropped unfertilized) were taken on three occasions (before, during and after cropping). Phospholipid fatty acids (PLFAs) were extracted from all soil samples and analysed for 12 C and 13 C contents in individual PLFAs. Seasonal variation in total PLFAs was small except for the most SOC‐rich treatment (sewage sludge). Weighted means of δ 13 C in PLFAs showed that the plots fertilized with calcium nitrate only had the largest δ 13 C values in PLFAs before (−20.24‰) and after the vegetation period (−20.37‰). However, during the vegetation period the values were much smaller (−21.85‰). This coincided with a strong increase in the PLFA 18:2ω6, 9, indicating the use of old organic matter by fungi. Monounsaturated PLFAs indicative of Gram‐negative bacteria were more frequent before and after the growing season. This observed 'rebound' effect of the δ 13 C PLFA values during the vegetation period indicates that seasonal turnover of the microbial biomass can be substantial.